Identification of blood-activating components from Xueshuan Xinmaining Tablet based on the spectrum–effect relationship and network pharmacology analysis. Issue 16 (10th March 2020) - Tan, Jing; Liu, Junli; Wang, Han; Zhang, Ying; Lin, Hongqiang; Wang, Zhongyao; Si, Hanrui; Zhang, Yutong; Liu, Jinping; Li, Pingya; Sun, Kai
Abstract : To identify active components of XXT and discuss the potential mechanism, the relationship between HPLC fingerprints and blood-activating effects were established by GRA and PLSR, and the mechanism was discussed by the network pharmacology analysis. Abstract : With the aim of identifying the active components of Xueshuan Xinmaining Tablet (XXT) and discussing the potential mechanism involved, the relationship between HPLC fingerprints and its blood-activating effect were established by multivariate statistical analysis, including gray relational analysis (GRA) and partial least squares regression analysis (PLSR). Network pharmacology was used to predict the potential mechanism based on the identified active components. GRA and PLSR analysis showed close correlation between the HPLC fingerprints and blood-activating activity, and peaks P1, P3, P11, P15, P22, P34, P36, P38 and P39 might be potential anti-blood stasis components of XXT. The pharmacological verification showed that salvianic acid A (P1), rutin (P3), ginsenoside Rg1 (P11) and Rb1 (P22), cinobufagin (P36), and tanshinone I (P38) and IIA (P39) had significant blood-activating effects. Based on these seven active compounds, network pharmacology analysis indicated that the anti-blood stasis effect of XXT might be closely related to TNF, PI3K-Akt and NF-κB signaling pathways. The spectrum–effect relationship of XXT was successfully established in this study. The blood-activating components and the anti-blood stasis mechanism were revealed and predicted. These findings could also be beneficial for an exploration of the active components of TCM.